Energy momentum consistent force formulation for the optimal control of multibody systems - Koch, Michael; Leyendecker, Sigrid (Proc. Appl. Math. Mech. (PAMM), 2010)
This work considers the optimal control of multibody systems being actuated with control forces which impact the system's motion directly. The goal is to find a dynamically feasible trajectory of states and control leading from an initial to a desired final state, while minimising an objective function. The optimal control problem is solved using a direct transcription method, i.e. boundary conditions and a discrete version of the equations of motion serve as constraints for the minimisation of a cost function with respect to the discrete state and control trajectory. Here, a particular time stepping scheme, an energy momentum integrator based on discrete derivatives is used. Corresponding to a constrained formulation of multibody systems, we develop an energy momentum consistent discrete force formulation that fits into the energy momentum integrato
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.ltd.energy